Hegemoni Kekuasaan dalam Novel Kawi Matin di Negeri Anjing Karya Arafat Nur - Bagus Dewadharu Megawayah Putra; Maria Matildis Banda; I Ketut Sudewa (Stilistika : Journal of Indonesian Language and Literature, 2023)
In this study, a novel Kawi Matin di Negeri Anjing by Arafat Nur is discussed. This study aims to describe the structure of the novel and the hegemony of the ruling class’s that found in the novel Kawi Matin di Negeri Anjing. The theory that been used is structural theory to analyze the plot, characters, and setting. The theory of hegemony of the ruling class is used to analyze hegemonic forms and the process of hegemony. The method that used to collect data is literature study with reading, listening, and note-taking techniques. Then, to analyze the data used descriptive analytical method by describing the result of data analysis that has been done. Structurally, the plot of novel Kawi Matin di Negeri Anjing contains the initial, middle, and final stages. The setting of place, time, and social support the formation of characters and the course of the story. The elements of plot, characters, and settings are having a relation that is interrelated with each other. The interrelation between these elements represents the hegemony of ruling class. Hegemony of ruling class contained in this novel is divided into three processes, such as cause, implementation, and effect. These three processes are found in the events that occur, such as rape, violence, murder, and sedition.